Software suite for the measurement of financial risk [Suite de Software para la Medición del Riesgo Financeiro] (2018)
In order to manage the different types of financial risks to which the entities of the sector are exposed on a daily basis, different national and international regulatory organizations have developed a set of monitoring and control tools in which the quantification of risks is vital for financial institutions as this allows calculating their probable losses, and subsequently allows defining and implementing procedures that contemplate the definition of general policies and risk mitigation. In coordination with these tools at the University of Medellin, a software tool called SICRIF has been developed, which has been designed as a suite composed of specialized modules that allow the quantification of liquidity risk, market risk and operational risk. © 2018 AISTI.